Access-Port Fixation on the Left Pectoral Fascia in Laparoscopic Adjustable Gastric Banding - van Wageningen, Bas (Springer-Verlag, 2010)
Access-port (AP) complications after laparoscopic adjustable gastric banding (LAGB) are often seen but seldom reported in literature. AP complications requiring additional surgery is reported in 3.6% to 24% of LAGB patients (Susmallian et al. Obes. Surg, 4:128–131, 2003; Peterli et al. Obes. Surg., 12(6):851–856, 2002; Busetto et al. Obes. Surg., 12:83–92, 2002; Mittermair et al. Obes. Surg., 19:446–450, 2009; Holeczy et al. Obes. Surg., 9:453–455, 1999; Bueter et al. Arch. Surg., 393:199–205, 2008; Launay-Savary et al. Obes Surg, 18:1406–1410, 2008; Balsiger et al. J. Gastrointest. Surg., 11:1470–1477, 2007; Szold and Abu-Abeid Surg. Endosc., 16:230–233, 2002). We evaluated the effect of fixing the AP on the pectoral fascia using the Velocity™ Injection Port on complication and re-operation rate. From January 2005 till October 2007, 619 LAGB procedures were performed using the SAGB QuickClose™. All procedures were performed by three dedicated surgeons using the pars flaccida technique. APs were placed on the fascia of the pectoral muscle using an infra-mammary incision. The AP device was fixed on the fascia using the Velocity™ Injection Port and Applier. Data was obtained retrospectively and records of 619 consecutive patients were reviewed for access-port complications. Sixty-eight AP complications were observed. Complications could be divided in four categories. Discomfort was reported in 30 patients, seven needing additional surgery. Infection contributed to 11 patients needing surgical removal of the device. Fourteen Patients with superficial infection were treated conservatively. Nine patients had inaccessible APs. Ultrasound-guided access was required in three patients. The remainder needed surgical relocation of the AP. Leakage of the tube was observed in four patients all of which needed revisional surgery. Our experience shows that fixation of the AP on the left pectoral fascia using the Velocity™ leads to a readily accessible AP with good anaesthetic and aesthetic results. In our series, 68 (11%) complications were recorded, of which 28 (4.5%) needed additional surgery.